The Role of Online Education in Encouraging Employee Empowerment in the Digital Era : A Study on E-commerce companies - Eri Mardiani; Eva Yuniarti Utami (Westscience Press, 2023)
In the rapidly evolving landscape of the digital age, employee empowerment within organizations has become a critical success factor. This research explores the role of online education in enhancing employee empowerment, focusing on an e-commerce company operating in Indonesia. A quantitative method approach, and a quantitative survey to collect data from 100 respondents. Findings showed that most participants perceived the online education program to have a positive impact on their empowerment. This perception underscores the value of online education in providing employees with the necessary skills, knowledge and autonomy to thrive in the digital age. This study contributes valuable insights for organizations looking to leverage online education as a means to empower their workforce and navigate the challenges of the digital age.